2013
DOI: 10.3389/fnbeh.2013.00180
|View full text |Cite
|
Sign up to set email alerts
|

Simulating real world functioning in schizophrenia using a naturalistic city environment and single-trial, goal-directed navigation

Abstract: Objective: To develop a virtual reality platform that would serve as a functionally meaningful measure of cognition in schizophrenia and that would also complement standard batteries of cognitive tests during clinical trials for cognitive treatments in schizophrenia, be amenable to human neuroimaging research, yet lend itself to neurobiological comparison with rodent analogs.Method: Thirty-three patients with schizophrenia and 33 healthy controls matched for age, sex, video gaming experience, and education com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 81 publications
3
24
0
1
Order By: Relevance
“…Our results were also consistent with recent studies demonstrating that VR training using animated avatars can be used to improve vocational and social skills for individuals with psychiatric disabilities (Park et al, 2011; Rus-Calafell et al, 2014; Tsang et al, 2013; Zawadzki et al, 2013). Moreover, VR-JIT provided in-the-moment feedback, was rewarding, and was designed using behavioral learning principles with repetitive practice that allowed participants to build mastery as the simulated interviews progressively increased in difficulty.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results were also consistent with recent studies demonstrating that VR training using animated avatars can be used to improve vocational and social skills for individuals with psychiatric disabilities (Park et al, 2011; Rus-Calafell et al, 2014; Tsang et al, 2013; Zawadzki et al, 2013). Moreover, VR-JIT provided in-the-moment feedback, was rewarding, and was designed using behavioral learning principles with repetitive practice that allowed participants to build mastery as the simulated interviews progressively increased in difficulty.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, VR training is a strategy that the field is developing to improve social cognition and assess community-based outcomes (Rus-Calafell et al, 2014; Zawadzki et al, 2013). This study demonstrated preliminary evidence that a VR approach to training job interview skills might be a feasible and efficacious tool to improve job interview performances and self-confidence in job interviewing for individuals with psychiatric disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Effect sizes of the within-group changes in the VR-JIT and wait-list TAU groups were consistent with the effects observed among individuals with SMI or ASD who used VR-JIT training (Smith et al, 2014a, 2014b) and that of other studies that used animated avatars to improve social skills for individuals with psychiatric disabilities (Park et al, 2011; Rus-Calafell et al, 2014; Tsang & Man, 2013; Zawadzki et al, 2013). …”
Section: Discussionsupporting
confidence: 79%
“…16 Cognitive problems in goal-directed navigation were also found in naturalistic virtual environments such as finding targets in a city. 17 Compared to healthy controls, schizophrenia patients were less flexible in changing strategies for finding the best bus route, 18 were slower and less successful in a shopping task 19 and had poorer medication management skills in a virtual apartment. 20 VR enables to investigate interactions between individual and social environment in great detail.…”
Section: Cognition and Social Behaviormentioning
confidence: 99%